An Overview of Target Specific Neuro-Protective and Neuro-Restorative Strategies - Mutairy, Ahmad Al; Moutaery, Khalaf Al; Asmari, Abdulrahman Al; Arshaduddin, Mohammed; Tariq, Mohammad (IntechOpen, 2012)
None